Overview of the Diversity, Phylogeny and Biogeography of Strombidiid Oligotrich Ciliates (Protista, Ciliophora), With a Brief Revision and a Key to the Known Genera - Song, Wen; Xu, Dapeng; Chen, Xiao; Warren, Alan; Shin, Mann Kyoon; Song, Weibo; Li, Lifang (Frontiers in Microbiology, 2021)
Strombidiids are common free-living ciliates that have colonized coastal and open oceanic waters across the world. In recent years, numerous new taxa and gene sequences of strombidiids have been reported, revealing a large diversity of both their morphologic and genetic features. Here, we compare the taxonomic characters of all genera in the family Strombidiidae, provide a key to their identification, and investigate their molecular phylogeny. In addition, we analyse their regional distribution based on faunal data accumulated in China and attempt to infer their global distribution based on SSU rRNA gene sequence data. The current work revises the systematics of strombidiids based on morphologic, phylogenetic and biogeographic evidence, and provides a genus-level review of marine strombidiids.